2017
DOI: 10.1016/j.burns.2017.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Agents, mechanisms and clinical features of non-scald burns in children: A prospective UK study

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Methods: A prospective cross-sectional study was conducted across Cardiff, Bristol and Manchester, including six emergency departments, three minor injury units and one burns unit between 13/01/2013-01/10/2015. Data collected for children aged <16 years with any burn (scald, contact, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Scalds and contact burns were also usually smaller in size than flame burns. Another study of non‐scald burns in children from the UK found that only 6.5% of contact burns were full thickness 17 . An epidemiologic study of burns and scalds in children from South Wales found that most inpatient injuries were due to scalds while most outpatient injuries were due to contact burns 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Scalds and contact burns were also usually smaller in size than flame burns. Another study of non‐scald burns in children from the UK found that only 6.5% of contact burns were full thickness 17 . An epidemiologic study of burns and scalds in children from South Wales found that most inpatient injuries were due to scalds while most outpatient injuries were due to contact burns 18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, prevention strategies should be used to educate parents and schools of young children regarding the safe use of portable household devices and electrical cords. Older school-aged children should be educated at school [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The Burns & Scalds Assessment Tool (BaSAT) informs a number of studies (see Supplement S1 in the online Supporting Information). It is an evidence‐based proforma (Bennett et al, 2019; Johnson et al, 2017; Kemp et al, 2014, 2018) used by clinicians to standardise the documentation of clinical assessments of children with a burn. The BaSAT was introduced following training in three EDs (Bristol Royal Hospital for Children, University Hospitals Bristol NHS Trust, North Bristol NHS Trust and the Paediatric ED, University Hospital of Wales), two minor injuries units (MIUs) (North Bristol NHS Trust and Barry Community Hospital, South Wales) and the ED at the South West UK Children's Burns Centre in Bristol in 2013–14.…”
Section: Methodsmentioning
confidence: 99%